1986
DOI: 10.1016/0014-5793(86)81504-6
|View full text |Cite
|
Sign up to set email alerts
|

Conformational changes in C1q upon binding to IgG oligomers

Abstract: The interaction between Clq and immune complexes is inhibited by 1-anilino-8-naphthalenesulfonate (ANS) in the concentration range of 2-4 mM. ANS binds to Clq with a 20-fold higher afl]nity than to IgG [(1986) Mol. Immunol. 23, 39-44] and therefore it is possible to label only Clq with ANS in the presence of lgG. Under such conditions no inhibition is observed. Addition of monomer IgG to a solution of C lqbound ANS did not significantly alter the fluorescence of the ANS. However when oligomeric IgG was added … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

1990
1990
2020
2020

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…It has previously been shown that C1q changes conformation upon binding to aggregated Igs [4, 55]. We have found that this conformational change permits specific interaction with calreticulin, and we propose that a similar conformational change occurs when C1q is immobilized on the polystyrene surface of ELISA plates or is heat treated for a short period of time.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…It has previously been shown that C1q changes conformation upon binding to aggregated Igs [4, 55]. We have found that this conformational change permits specific interaction with calreticulin, and we propose that a similar conformational change occurs when C1q is immobilized on the polystyrene surface of ELISA plates or is heat treated for a short period of time.…”
Section: Discussionmentioning
confidence: 61%
“…C1q binds to altered conformations of Ig, immunecomplexes, and aggregated Igs, for example, bound to bacterial surfaces [54]. We hypothesized that an altered conformation of C1q, reported to be induced by binding to IgG or IgM [4,55], would allow calreticulin to recognize C1q, and this was confirmed by several experiments (Fig. 1A).…”
Section: Binding To Immunoglobulins Induces a Conformational Change Imentioning
confidence: 55%
“…Hansen, N. Thielens, G. Arlaud, L. Kongerslev, S. Thiel, P. Højrup, G. Houen, unpublished observations). C1q has previously been shown to undergo a conformational change upon binding to a solid surface or aggregated IgG thus allowing interaction with calreticulin [19, 20]. Similarly, upon binding to the solid phase of the microtitre plates, CD40L changes conformation, thus allowing interaction with calreticulin, which itself changes conformation upon binding as evidenced by the binding characteristics.…”
Section: Discussionmentioning
confidence: 99%
“…Calreticulin is an endoplasmic reticulum (ER) chaperone, which has also been reported to be present at the cell surface in complex with various receptors and to function as a co-receptor for these, thereby mediating internalization of apoptotic cells, pathogens and aggregated immunoglobulins bound to collectins or C1q [1,[9][10][11][12][13][14][15][16][17][18]. Notably, the interaction between calreticulin and C1q has been found to depend on structural changes in C1q, such as it occurs upon the binding of C1q to a surface or to aggregated immunoglobulins [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…This produces a curve similar to a DSC thermogram, which can be used to evaluate excipients for their ability to modulate thermal stability [79]. ANS fluorescence has been used for other related purposes, such as the investigation of protein interactions with ligands [80] and toxins [48], or detecting conformational changes related to binding sites [49].…”
Section: Techniques To Analyse Protein 3° Structurementioning
confidence: 99%